包含作为抗气体迁移剂的聚合物微凝胶的水泥基组合物 (2025)
本发明涉及固井技术领域，特别是在油井和/或气井或地热能的建设中。更具体地，本发明的主题是一种水泥基组合物和一种改进的固井方法，其方法是在水泥中引入一种聚合物微凝胶作为抗气体迁移剂。 The present invention concerns the technical field of cementing, in particular in the construction of oil and/or gas wells or geothermal energy. More specifically, the subject of the present invention is a cementitious composition and an improved method of cementing by means of the introduction into the cement of a polymeric micro-gel as an anti-gas migration agent.